Gastroesophageal reflux (GER) in preterms: current dilemmas and unresolved problems in diagnosis and treatment - Kültürsay, Nilgün (The Turkish Journal of Pediatrics, 2012)
Gastroesophageal reflux (GER) is a common physiologic phenomenon in preterm infants. Many infants remain asymptomatic, and the diagnosis of GER is difficult since clinical signs and symptoms are nonspecific. Diagnosis can also be difficult due to technical limitations. None of the currently available agents has been proven to prevent regurgitation. The efficacy and safety of gastroesophageal reflux disease (GERD) therapy have not been studied systematically in preterm infants. Therefore, clinicians must consider the risks and benefits of therapy. Preventive measures should be the firstline intervention. Prone, head upward and left-side positioning may reduce symptoms, but infants must be discharged home in the supine position. Thickening of feeds may be harmful in preterm infants. Frequent small-amount or continuous-drip feeding, short-term trial of hypoallergenic formula and probiotics are among the proposed treatments. Infants with severe symptoms and those who do not respond to the conservative and medical treatment need further diagnostic evaluation and very rarely a Nissen fundoplication.